Optimalisasi Literasi Keuangan di Komunitas Online untuk Penguatan Kapasitas Finansial Rumah Tangga - Rahmawati, Apriana; Rizky Prasetya; Alif Faruqi Febri Yanto (Politeknik Piksi Ganesha Indonesia, 2026)
The financial literacy gap among Indonesian women, particularly housewives who shoulder primary responsibility for household financial management, presents a pressing concern that motivated this community service program. Employing a participatory action research (PAR) approach through WhatsApp-based lectures, the program was designed to strengthen financial literacy knowledge, encourage positive financial behavioral change, and improve the financial well-being of S****.id community members. Program material covered six core topics: budgeting, saving and emergency funds, debt management, basic investment, long-term financial planning, and financial goal setting. A total of 87 out of 124 participants completed the full program series, yielding a 70.2% retention rate. Average financial literacy scores rose from 46.4% to 73.4% (gain score +27.0 points), all financial behavior indicators showed significant improvement, and the post-program financial well-being index reached 62.37—accompanied by a meaningful growth in financial agency and transformative women's empowerment.